DRONE UNTUK PERCEPATAN PEMETAAN BIDANG TANAH - budi utomo (Media Komunikasi Geografi, 2017)
Abstract Since 2016 the government has accelerated the registration of land systematically complete until in 2025 the whole plot of land in Indonesia registered. In 2018 alone the government is targeting 7 million fields, and 2019 is targeting 9 million. To achieve these targets is required technology that can overcome this. Drone, better known as Unmanned Aerial Vehicle (UAV) or unmanned aircraft technology as a solution for mapping of land with a large target, time and area flexibility desired shooting, and detailed shooting spatial resolution results as well as a relatively cheaper cost than the recording price with satellite. This research uses qualitative method. Data were obtained from the study literature. After the data collected it will be done data analysis with three stages, namely; Reduction, Display, and Conclution. The results of this study shows that the use of drones for the acceleration of land mapping is the right choice because the drone shots have spatial resolution which is so high that it complies with ground mapping rules and the price is cheap. Keywords: drone, mapping, plot of land